Application of Experimental Design Approach in optimization of Quality parameters of Calcium- and Magnesim-enriched Milk - Anastasova, Liljana; Petreska ivanovska, Tanja; Andrijana Ancevska; Petkovska, Rumenka; Petrushevska tozi, Lidija (Meral Publisher, 2022)
Full factorial (23) design was applied to evaluate the effects of addition of calcium chloride, magnesium chloride, and time of magnetic stirring on quality parameters of milk in the preparation process of calcium- and magnesium-enriched milk. The quality of the mineral enriched milk was evaluated in terms of relative density, dry matter, titratable acidity, the content of proteins, lipids, and carbohydrates as well as the content of calcium, magnesium, and phosphorus, and calcium: phosphorus ratio. In parallel, sensorial properties were analyzed to select the most preferable sample for consumers. The results from the experimental design and the sensorial analysis indicated that the application of medium levels of calcium and magnesium salts for milk enrichment provides acceptable quality and sensory characteristics similar to commercial milk. The determined content of calcium and magnesium in these samples was sufficient to give an additional 9.0% of the recommended daily allowance (RDA) for calcium (700 mg/day) and 2.6% of the RDA for magnesium (300 mg/day). Enrichment with calcium more than 0.3 g/100 g was inadequate in respect to certain quality parameters, and also off-flavors were developed during the first five days of the cold storage. The PCA was efficient in identifying and measuring the attributes of functional milk important for consumer acceptability. This study constitutes a step forward in developing strategies for the preparation of functional milk with increased nutritional value and favorable sensory profile that can be used as a vehicle for delivering more minerals to the human body.
Keywords: International Journal of Pharmaceutical and Phytopharmacological Research (eIJPPR) | February 2022 | Volume 12 | Issue 1 | Page 7-16 LIljana Anastasova, Application of Experimental Design Approach in Optimization of Quality Parameters of Calcium- and Magnesium-Enriched Milk ISSN (Online) 2249-6084 (Print) 2250-1029 www.eijppr.com Application of Experimental Design Approach in Optimization of Quality Parameters of Calcium- and Magnesium-Enriched Milk LIljana Anastasova1*, Tanja Petreska Ivanovska2, Andrijana Ancevska2, Rumenka Petkovska1, LIdija Petrushevska-Tozi2 1Institute of Applied Chemistry and Pharmaceutical Analysis, Faculty of Pharmacy, University of Ss. Cyril and Methodius, Skopje, Republic of North Macedonia 2Institute of Applied Biochemistry, Faculty of Pharmacy, University of Ss. Cyril and Methodius, Skopje, Republic of North Macedonia. ABSTRACT Full factorial (23) design was applied to evaluate the effects of addition of calcium chloride, magnesium chloride, and time of magnetic stirring on quality parameters of milk in the preparation process of calcium- and magnesium-enriched milk. The quality of the mineral enriched milk was evaluated in terms of relative density, dry matter, titratable acidity, the content of proteins, lipids, and carbohydrates as well as the content of calcium, magnesium, and phosphorus, and calcium: phosphorus ratio. In parallel, sensorial properties were analyzed to select the most preferable sample for consumers. The results from the experimental design and the sensorial analysis indicated that the application of medium levels of calcium and magnesium salts for milk enrichment provides acceptable quality and sensory characteristics similar to commercial milk. The determined content of calcium and magnesium in these samples was sufficient to give an additional 9.0% of the recommended daily allowance (RDA) for calcium (700 mg/day) and 2.6% of the RDA for magnesium (300 mg/day). Enrichment with calcium more than 0.3 g/100 g was inadequate in respect to certain quality parameters, and also off-flavors were developed during the first five days of the cold storage. The PCA was efficient in identifying and measuring the attributes of functional milk important for consumer acceptability. This study constitutes a step forward in developing strategies for the preparation of functional milk with increased nutritional value and favorable sensory profile that can be used as a vehicle for delivering more minerals to the human body. Key Words: Mineral-enriched milk, Optimization, Design of experiments, Sensory acceptability